Mapping of lumbar multifidus stiffness Quantification in ankylosing spondylitis with shear-wave elastography - Mengyu Wang; Jia Liu; Lingcui Meng; Wen Fu; Jing Gao; Ruixia Ma; Yuxuan Luo; Yingjun Peng; Lihua Wu; Ziping Li (BMC Musculoskeletal Disorders, 2022)
Abstract Background Lower back pain and stiffness are the typical symptoms of ankylosing spondylitis (AS). In this study, muscle mass was assessed by muscle density, mechanical elasticity, and area. We investigated the characteristics of lumbar paraspinal-muscle (PSM) mass using muscle ultrasound shear-wave elastography (SWE), as well as the validity of this method for identifying patients with AS. Methods We recruited a representative cohort of 30 AS patients, and 27 healthy volunteers who were age- and sex-matched to the patient study group, investigated the Young’s modulus (YM), cross-sectional area (CSA) and thickness of lumbar multifidus (LM) muscle using SWE. This study did not need to be randomized. Data were collected at the department of ultrasonography of Guangdong Provincial Hospital of Chinese Medicine. We analyzed the data using SPSS version 18.0 (IBM Corp, Armonk, NY, USA). Normal distribution was evaluated by the Shapiro–Wilk test and Q–Q plots. Demographic and baseline data will be analyzed with standard descriptive statistics. Data will be presented as the mean ± standard deviation (SD). Non-normally distributed data are presented as medians with interquartile ranges (IQR). Results Young’s modulus (YM) of SWE in AS patients was significantly higher than that in volunteers. Percentage change in lumbar multifidus (LM) muscle cross-sectional area (CSA) and thickness were significantly lower in AS patients than in healthy volunteers on the left side of the body. Correlation analysis showed a positive correlation between percentage change in CSA and thickness in both volunteers and AS patients. In AS patients, YM was negatively correlated with percentage change of CSA and thickness on the right side, while increased disease duration in AS was associated with increased YM on the left. Conclusion AS patients showed reductions in LM muscle mass and function as the disease progressed, SWE could reflect these changes well. Trial registration. Chinese Clinical Trial Registry, ChiCTR2000031476. Registered 02/04/2020. http://www.chictr.org.cn/index.aspx .